Translating the diplomatic terminologys semantic expression in traditional Arabic - Ali Alshyiab, Monther Mohammad; Wan Sulong, Wan Muhammad; Abdul Jabar, Mohd Azidan; Mohd Kassim, Zalina (Human Resource Management Academic Research Society (HRMARS), 2023)
This research article explores the challenges and strategies involved in translating the semantic expression of diplomatic terminology in Traditional Arabic. Diplomatic discourse is characterized by its specialized terminology, which often presents difficulties in accurately conveying its meaning in translation. This study aims to examine the specific semantic challenges faced by translators when translating diplomatic terminology into Traditional Arabic and proposes effective strategies to overcome these challenges. By analyzing existing literature and case studies, this research contributes to the field of translation studies and provides practical insights for translators working in diplomatic contexts. Major Findings and Results: The research sheds light on the intricate syntactic and semantic structures of diplomatic terminologies in Traditional Arabic. The study underscores the profound cultural connotations and references intertwined with diplomatic terminologies in Traditional Arabic. The research critically assesses the current translations of diplomatic terminologies in Traditional Arabic. And Building upon the linguistic and cultural analysis, the research puts forward more accurate and contextually fitting translations of diplomatic terminologies in Traditional Arabic. Finally, Strategic adaptation of terminology, while upholding its core meaning, often involves techniques like paraphrasing, descriptive language, and culturally resonant analogies. These strategies bridge linguistic divides and faithfully transmit the intended message.